2020
DOI: 10.3390/jcm9041185
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy Using a New Folate Receptor-Targeted Photosensitizer on Peritoneal Ovarian Cancer Cells Induces the Release of Extracellular Vesicles with Immunoactivating Properties

Abstract: Often discovered at an advanced stage, ovarian cancer progresses to peritoneal carcinoma, which corresponds to the invasion of the serosa by multiple tumor implants. The current treatment is based on the combination of chemotherapy and tumor cytoreduction surgery. Despite the progress and standardization of surgical techniques combined with effective chemotherapy, post-treatment recurrences affect more than 60% of women in remission. Photodynamic therapy (PDT) has been particularly indicated for the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
(46 reference statements)
4
16
1
Order By: Relevance
“…Intraoperative illumination at an appropriate wavelength results in activation of the photosensitizer which is responsible for a photobiological reaction leading to the formation of cytotoxic reactive oxygen species. This results in the death of the tumor cells and a potential abscopal effect mediated by the release of extracellular vesicles with immune-activating properties [ 14 , 39 ]. Its double selectivity (photosensitizer specificity for the tumor and activation controlled by illumination) means there are no distant systemic effects which represents a theoretical advantage over HIPEC.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative illumination at an appropriate wavelength results in activation of the photosensitizer which is responsible for a photobiological reaction leading to the formation of cytotoxic reactive oxygen species. This results in the death of the tumor cells and a potential abscopal effect mediated by the release of extracellular vesicles with immune-activating properties [ 14 , 39 ]. Its double selectivity (photosensitizer specificity for the tumor and activation controlled by illumination) means there are no distant systemic effects which represents a theoretical advantage over HIPEC.…”
Section: Discussionmentioning
confidence: 99%
“…CELL‐LEF was already used in experimental studies to evaluate a new folate receptor‐targeted photosensitizer on peritoneal ovarian cancer cells [19] and in four pancreatic adenocarcinoma (ADKP) i cell lines: Capan‐1, Capan‐2, MiapaCa‐2 and Panc‐1. [20]…”
Section: In Vitro Use Of Lef: Cell‐lefmentioning
confidence: 99%
“…Moreover, active targeting may be explored for the intraperitoneal administration of photosensitizers, which could significantly reduce the systemic causes of PDT-associated morbidity [ 45 , 88 ]. Although some candidate epitopes for molecular targeting have been identified for ovarian cancer [ 89 ], more studies are required to identify suitable targets for PCAR of colorectal, pancreatic and gastric origins. For ALA, biomodulation strategies to increase endogenous PpIX production as described for PDD may have similar relevance to augmenting the efficacy of ALA-PDT.…”
Section: Photodynamic Therapy For Peritoneal Carcinomatosismentioning
confidence: 99%
“…The photosensitizer pyropheophorbide conjugated to folate was demonstrated to be effective in binding ovarian cancer cells in a rat model of ovarian PCAR, with a reported tumor-to-normal ratio of 9.6 [ 62 ]. Follow-up studies showed the effective PDT of ovarian and pancreatic cancer cell lines in vitro using this folate-conjugated photosensitizer [ 89 , 91 ], indicating that this targeting strategy may have relevance for pancreatic PCAR as well.…”
Section: Photodynamic Therapy For Peritoneal Carcinomatosismentioning
confidence: 99%